2017
DOI: 10.1111/nmo.13243
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an algorithm‐based approach to the diagnosis and management of functional gastrointestinal disorders: A pilot trial

Abstract: Background: Recent advances in the development of diagnostic criteria and effective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…For patients with non‐specific lower gastrointestinal symptoms, FC testing reduces the risk of missing an organic GID and ensures prompt specialist review if required. A recent Australian study found that FC testing, combined with a routine panel of blood tests, identified patients who needed prompt review by a specialist, improving the safety of local triage practices . By excluding organic GID, findings of non‐elevated FC levels also enable early and reliable diagnosis of a functional GID by general practitioners without gastroenterology referral or further testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with non‐specific lower gastrointestinal symptoms, FC testing reduces the risk of missing an organic GID and ensures prompt specialist review if required. A recent Australian study found that FC testing, combined with a routine panel of blood tests, identified patients who needed prompt review by a specialist, improving the safety of local triage practices . By excluding organic GID, findings of non‐elevated FC levels also enable early and reliable diagnosis of a functional GID by general practitioners without gastroenterology referral or further testing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Australian study found that FC testing, combined with a routine panel of blood tests, identified patients who needed prompt review by a specialist, improving the safety of local triage practices. 42 By excluding organic GID, findings of non-elevated FC levels also enable early and reliable diagnosis of a functional GID by general practitioners without gastroenterology referral or further testing. Confident diagnosis of a functional GID in primary care is likely to improve patient acceptance of their diagnosis and their uptake of effective management.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this knowledge gap, two of these reviews provide clinical guidelines for the implementation of dietary therapies including a low FODMAP diet . Despite these concerns, in a proof‐of‐concept study, an algorithmic approach to diagnosis and management prior to the assessment by a specialist was evaluated and patient introduction of a low FODMAP was reported to be effective …”
mentioning
confidence: 99%
“…2,3 Despite these concerns, in a proof-of-concept study, an algorithmic approach to diagnosis and management prior to the assessment by a specialist was evaluated and patient introduction of a low FODMAP was reported to be effective. 4 One of the ongoing issues regarding the low FODMAP diet is its complexity and patient compliance. The low FODMAP diet is designed in three stages, starting with short-term (4-8 weeks)…”
mentioning
confidence: 99%
“…In view of this knowledge gap, two of these reviews provide clinical guidelines for the implementation of dietary therapies including a low FODMAP diet . Despite these concerns, in a proof‐of‐concept study, an algorithmic approach to diagnosis and management prior to assessment by a specialist was evaluated and patient introduction of a low FODMAP was reported to be effective .…”
mentioning
confidence: 99%